Administrative discretion in states of full democracy and hybrid regime (on example of Germany and Ukraine) - Bakhtina, Iuliia S. (P.A. Persona e Amministrazione, 2023)
The urgency of the study is stipulated by the need to clarify the features of administrative discretion in states with different democracy indices (different political regimes) and to describe the verification of compliance with the limits of discretion. The purpose of the article is to make clear the correlation between the understanding and administrative discretion boundaries and the type of a state according to the level of democracy development. The research is based on the democracy index, determined annually by the Economist Intelligence Unit, according to which states are divided into four types: full democracies, flawed democracies, hybrid regimes, and authoritarian regimes. A comparative method, which was used to compare the perception of administrative discretion in Germany and Ukraine as typical states of full democracies and hybrid regimes, is the basis of the research. The article clarifies that administrative discretion should be understood as a way of exercising the powers of administrative authorities, which involves choosing one of several possible options for behavior in a specific case and is carried out in compliance with the rule of law, human rights, principles of administrative procedures, and the purpose of powers; it is substantiated that in the states of hybrid regimes the institution of administrative discretion is poorly developed, there are no clear criteria for the discretion boundaries, the issue of judicial control over decisions made with the use of discretion is uncertain; there is excessive bureaucracy. The materials of the article can be used for administrative discretion scientific research, and algorithms for checking compliance with discretionary limits. The main provisions of the article can become guidelines for hybrid regime states to improve legislation in the area of discretion implementation.